PEMAHAMAN NASABAH PERBANKAN SYARIAH TERHADAP PENYELESAIAN SENGKETA PASCA PUTUSAN MK NO. 93/PUU-X/2012 - Andhika Nur Wicaksana; Mohammad Adnan (Universitas Sebelas Maret, 2019)
This paper aims to examine about understanding customers on dispute resolution on Islamic banking under the existence of a ruling of the Constitutional Court the number 93/PUU-X/2012. Research conducted is a non doctrinal research research where to find out the circumstances occur in practice. In this study, which examined secondary data is initially, then proceed with the examination of the primary data in a field, or against society. The results of this study suggest that an understanding of the customer regarding the dispute on Islamic banking is very less in terms of regulation governing that Act No. 21 of the year 2008 about Islamic banking whereas in article 55 paragraph (2) are described clearly as to how and in what ways can the customer if there is a dispute in the future, and also the customer also don't know and understand about the existence of the constitutional court verdict number 93/PUU-X/ 2012 concerning the judicial review against the laws of Sharia banking, where the constitutional court verdict related dispute resolution problem Islamic banking which finally gives a certainty the law against the competency of the courts authorized to resolve the dispute over Islamic banking.Keywords:Islamic Banking, Dispute Resolution, Customer